"UZBEKISTAN-2030" STRATEGY: IS BECOMING THE MAIN CRITERIA OF BUILDING AN INTERNATIONAL STATE IN THE NEW UZBEKISTAN (World Bulletin of Social Sciences, 2024)
In this article, the "Uzbekistan-2030" strategy and the main goals of its implementation in the Republic of Uzbekistan, the prospects for the gradual and organic development of all sectors in our country, the main and priority ones that should be implemented in our country in the near future in the era of world globalization thought about tasks.